1988
DOI: 10.1007/bf01064244
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and demographic characteristics of 15 patients with repetitively assaultive behavior

Abstract: The 15 patients with the highest numbers of assaultive incidents over a one year period in a state mental hospital were identified and information collected regarding a variety of clinical and demographic characteristics. The results showed a group of patients who are relatively young, manifest severe symptomatology that is generally unresponsive to treatment, and have now been hospitalized continuously for greater than four years. The patients experienced the onset of symptoms as teenagers in most cases, show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 36 publications
0
9
1
Order By: Relevance
“…The converse of this statement is also true: most psychiatric in-patients are not violent at all. Barber et al (1988) found that in a U S State hospital 15 long stay patients (average stay 4.5 years) accounted for alm ost half the total violence. A U K hospital survey, Noble and Rodger (1989), found that 91% of 1,529 admissions were not reported as being violent in any way.…”
Section: Repetitive Patternmentioning
confidence: 98%
“…The converse of this statement is also true: most psychiatric in-patients are not violent at all. Barber et al (1988) found that in a U S State hospital 15 long stay patients (average stay 4.5 years) accounted for alm ost half the total violence. A U K hospital survey, Noble and Rodger (1989), found that 91% of 1,529 admissions were not reported as being violent in any way.…”
Section: Repetitive Patternmentioning
confidence: 98%
“…Hodgekinson et al. (1985), who found that 5.3% of inpatients (fewer than 20% of the total number of assaultative patients) were responsible for over half of the assaults recorded over a 2‐year period and Barber et al. (1988), who found that 3.3% of patients accounted for 48.6% of assaults in a 1‐year period in a United States State Mental Hospital.…”
Section: Discussionmentioning
confidence: 99%
“…With de-institutionalization, the problem is inherited by inner city communities where most of these patients tend to segregate. Barber et al (1988) examined the clinical characteristics of 15 patients with repetitively assaultive behavior. These patients constituted 3.3 % of the average daily census but accounted for 48.6 % of all assaultive incidents during a 1-year period.…”
Section: Eeg and Institutional Aggression (Including Aggression In Scmentioning
confidence: 99%